“Did she just tap me?“: qualifying multisensory feedback for social touch during human-agent interaction in virtual reality - Richard, Grégoire; Boucaud, Fabien; Pelachaud, Catherine; Thouvenin, Indira (Frontiers in Virtual Reality, 2026)
Social touch is one of the many modalities of social communication. It can take many forms (from handshakes to hugs) and can convey a wide variety of emotions and intentions. Social touch is also multimodal: it is not only comprised of haptic feedback (both tactile and kinesthetic), but also visual feedback (gestures) and even audio feedback (sound of the hand movement on the body). Virtual agents (VA) can perceive and interact with users by making use of multimodality to express attitudes and complex emotions. There are still few studies that have investigated how to integrate touch into VAs’ social abilities, despite a growing interest in haptic interactions within immersive virtual environments (IVE). While prior work has examined haptic feedback, auditory substitution, or agent-based touch in isolation, no study has systematically disentangled the respective and combined contributions of visual, auditory, and tactile cues to the perception of being socially touched by a virtual agent. To address this gap, we conducted three experiments that progressively isolate and combine modalities, revealing how each shapes touch recognition, believability, and agency attribution. Taken together, our results show that multisensory feedback improves experience of social touch, which is in line with previous research in IVEs. They also show that visual feedback has the potential to guide the recognition of the stimulus the most but both audio and tactile feedback further help disambiguate the recognition of a touch gesture in particular cases. The results also show that both level of animation and interpersonal distance are essential to how much the VA is felt as a social agent when initiating touch. While visual feedback and tactile feedback are the main contributors to participants feeling touched by the VA, audio feedback also has a significant impact.